Osteochondral Injuries of the Knee in Pediatric Patients - Bauer, Kathryn L. (The Journal of Knee Surgery, 2018)
Osteochondral injuries in pediatric patients may occur as a result of a traumatic injury or secondary to an osteochondritis dissecans (OCD) lesion. Lateral patella dislocation is a common traumatic cause of osteochondral injury that typically occurs at the medial facet of the patella or at the lateral aspect of the distal femur. Multiple theories have been proposed for the cause of an OCD lesion in the knee, including trauma or repetitive microtrauma, local vascular insufficiency, and family history. The most “classic” location for OCD lesions of the knee is the lateral aspect of the medial femoral condyle of the distal femur. Multiple treatment options are available for both traumatic osteochondral injuries and OCD lesions, with important determining factors of treatment being skeletal maturity of the patient, instability of the fragment, lesion location, and size of the lesion. Nonsurgical management is appropriate in some situations. Surgical options range from simple fragment excision to internal fixation of the fracture fragment to more complex cartilage restoration or replacement procedures. This special focus section will discuss the diagnosis and treatment options for traumatic osteochondral knee injuries, including the subset secondary to juvenile OCD lesions.
Keywords: osteochondral injury; articular cartilage; osteochondritis dissecans; osteochondral allograft; patellar dislocation